Effects of carvedilol and metoprolol on the myocardium during mechanical unloading in a rat heterotopic heart transplantation model. (22nd August 2021) - Kim, Geena; Kil, Hong Ryang; Quan, Cheng; Lee, Sang Su
Abstract: Background and objectives: Left ventricular assist devices enable recovery from severe heart failure and serve as a bridge to heart transplantation. However, chronic mechanical unloading can impair myocardial recovery. We aimed to assess myocyte size, fibrosis, apoptosis, and β-adrenoreceptor levels after rats with left ventricle unloading induced by heterotopic heart transplantation were administered carvedilol and metoprolol. Methods: Thirty rats with heart transplants were divided randomly into control, carvedilol treatment, and metoprolol treatment groups. Follow-up was conducted after 2 and 4 weeks of unloading. Results: Carvedilol and metoprolol treatments did not prevent the decrease in myocyte diameter in unloaded left ventricles. Metoprolol significantly decreased the ratio of the fibrotic area in the unloaded heart, measured using Masson's trichrome staining after 2 weeks. However, carvedilol and metoprolol did not reduce apoptosis, based on measurements of terminal deoxynucleotidyl-transferase-mediated dUTP nick end-labelling positive cells and the expression of caspase-3 in unloaded hearts after 2 and 4 weeks. Metoprolol treatment did not significantly decrease the mRNA expression of myocardial SERCA2a in the unloaded heart after 2 weeks. Conclusions: Compared to carvedilol treatment, metoprolol treatment improved myocardial fibrosis and SERCA2a expression to a greater extent; however, neither drug prevented myocardial apoptosis.